Photonic Computer: A Next Generation of Computer World - Bhattarai, Lakshmi Nath (Himalayan Physics, 2011)
Software in the computer is used to study from sub-atomic particles to lagre scale strucute like galaxies. Computer technology found to make computer small and as fast as possible. As photon travel tansfer than electric curren, time required for computation in photonic computer will be highly reduced and portable. Keywords: Sub-atomic particles; Photon travel tansfer The Himalayan Physics Vol.2, No.2, May, 2011 Page: 65-66 Uploaded Date: 1 August, 2011